OP0201-HPR Development of user- focused standards of care for rheumatoid arthritis the www.eumusc.net project - work package 5. (23rd January 2014) - Stoffer, M.; Smolen, J.; Woolf, A.; Stamm, T.
Abstract : Background: The EUMUSC.net project facilitates cooperation between EU Member States and promotes a comprehensive European strategy to optimise musculoskeletal health. Objectives: The purpose of Work package 5, as a part of the EUMUSC.net project, was to develop evidence based and user-focused standards of care (SOC), for Rheumatoid Arthritis (RA). Methods: A systematic review of international documents covering SOC for RA was conducted. National scientific societies, social leagues and health professional associations were contacted via the EULAR secretariat and asked to provide relevant documents. Documents concerning pharmacological and non-pharmacological interventions published after 2002 were included. The obtained documents were evaluated based on the AGREE II criteria (www.agreetrust.org ). All recommended methods to treat RA were extracted, as well as information on them and all recommendations given. Each of these methods was discussed in a consensus group meeting of 21 EUMUSC.net researchers and patient representatives from different countries regarding priority and relevance in their home countries as well as possible interrelation with other methods. A scheme was developed with groups of interventions and formulated in a way that could be understood by users. To this end, conventional DMARDs, biological agents, NSAIDs, were grouped under pharmacological treatment. Giving up smoking, weight control and physical activity were grouped under Lifestyle Interventions. Results: 49 types of therapies or other interventions, such as DMARDs, biological agents, exercise based-, activity based interventions, were extracted from the documents and could be grouped into seven types of interventions, namely Pharmacological Treatment, Monitoring, Lifestyle Interventions, Surgery, Education/Information/Self Management, Non- Pharmacological Treatment and Access to care. From these data 16 user-focused standards of care were formulated. Conclusions: The lay version of the user-focused SOC will be available in all 23 official languages of the European Union for the information of people with RA across all member states. This work should contribute to the harmonization of RA treatment in Europe. Disclosure of Interest: None Declared